Families of the mentally ill : coping and adaptation - Hatfield, Agnes B; Lefley, Harriet (Guilford Press, 1987)
With current trends toward family care of individuals with major mental illness, it is now generally accepted that families need a firm knowledge base and a wide range of skills in order to cope with a mentally ill relative. Toward this end, educational programs are developing all over the country. However, little attention has been given to education as a discipline nor to the contributions that educational psychology can make to more effective instruction and skill development. A resource that will help professionals become more effective family educators, this is the first book to delineate the key elements for creating curricula in family education by combining what is known about mental illness with essential principles of education.
Keywords: Family Relations; adaptace psychologická; Mental Disorders; psychologie, klinická psychologie; Family Characteristics; Adaptation, Psychological; charakteristiky rodiny; rodinné vztahy; duševní poruchy